Classical myth in four films of Alfred Hitchcock - Padilla, Mark William (Lexington Books, 2016)
This book explores the themes and symbols of classical myth and literature reflected in Alfred Hitchcock's films. Mark W. Padilla examines the classical resonances of four movies, one from each of the filmmaker's first decades.